The impact of airborne ultrafine particulate matter on human keratinocyte stem cells. (3rd March 2023) - Labarrade, Florian; Meyrignac, Céline; Plaza, Christelle; Capallere, Christophe; Botto, Jean‐Marie; Imbert, Isabelle
Abstract: Objective: Air pollution is today fully acknowledged to be a significant public health problem. Rapid urbanization exposed us to a variety of unhealthy ambient air pollutants at high concentrations. The emergence of airborne ultrafine particles has added an additional dimension to this already complex problem of air pollution. The skin has different functions, one of them being the protection against the deleterious effect of external agents. The aim of this study is to evaluate the impact of airborne ultrafine particles (UFP) pollution on skin aging and on keratinocyte differentiation. Methods: Ex vivo human skin biopsies and cultured keratinocytes stem cells (KSC) were submitted to diesel exhaust‐derived UFP. Reactive oxygen species (ROS) production was assessed with the MitoSOX™ probe. Keratinocyte stemness potential was evaluated by the immunodetection of keratin 15 (K15) and p63 (∆N isoforms). Effect of UFP on the epithelial niche maintenance was evaluated by immunodetection of Sox9. Reconstructed epidermis model was used to assess the impact of UFP on keratinocyte differentiation and aging. Results: UFP exposure induced ROS production and disturbed K15, ∆Np63 and Sox9 expression in KSC or ex vivo skin. Finally, investigations on reconstructed epidermis revealed a phenotype marked by impaired keratinocyte differentiation. Conclusion: These results indicate that UFP pollution is a potent extrinsic factor of skin aging, affecting the keratinocyte stem cell potential and the skin renewal process. Abstract: Objectif: La pollution de l'air est désormais pleinement reconnue comme un problème de santé publique important. L'urbanisation rapide nous a exposés à une variété de polluants atmosphériques ambiants malsains à des concentrations élevées. L'émergence de particules ultrafines en suspension dans l'air a ajouté une dimension supplémentaire à ce problème déjà complexe de la pollution de l'air. La peau exerce différentes fonctions, l'une d'elles étant la protection contre l'effet délétère d'agents extérieurs. L'objectif de cette étude est d'évaluer l'impact de la pollution par les particules ultrafines (UFP) aéroportées sur le vieillissement cutané et sur la différenciation des kératinocytes. Méthodes: Des biopsies de peau humaine ex vivo et des kératinocytes souches (KSC) en culture ont été mis en présence d'UFP provenant d'échappement de véhicule diesel. La production d'espèces réactives de l'oxygène (ROS) a été évaluée avec la sonde MitoSOX™. Le potentiel de souche des kératinocytes a été évalué par immunodétection de la kératine 15 (K15) et p63 (isoformes ∆N). L'effet des UFP sur la niche épithéliale a été évalué par immunodétection de Sox9. Un modèle d'épiderme reconstruit a été utilisé pour évaluer l'impact des UFP sur la différenciation et le vieillissement des kératinocytes. Résultats: L'exposition aux UFP a induit la production de ROS, a perturbé l'expression de K15, ∆Np63 et de Sox9 dans les KSC et dans la peau ex vivo. Enfin, des investigations sur des épidermes reconstruits ont révélé un phénotype marqué par une différenciation altérée des kératinocytes. Conclusion: Ces résultats indiquent que la pollution par les UFP est un facteur extrinsèque puissant du vieillissement cutané, affectant le potentiel des cellules souches de kératinocytes et le processus de renouvellement cutané. Abstract : Ultrafine particles exposure reduced Sox9 expression in human keratinocyte stem cells.